What is a virus? - Daynes , Katie; Beautyman , Kirsti (London Usborne Publishing Ltd, 2021)
All the big questions children are asking about viruses (and adults are struggling to answer) are covered in this much-needed addition to the ever-popular First Questions & Answers series. Our lives have been taken over by a tiny germ we can't even see. It's time to explain to young children (and their parents and carers) what's really going on. What IS a virus? How do viruses spread? Why should everyone keep washing their hands? How does a vaccine work? And what can we do to STAY WELL? All these questions and more are answered in a friendly and helpful way, with quirky illustrations and of course lots of flaps to lift
Science
Keywords: Children Health and hygiene; Communicable diseases